Sociolinguistic Profile of Sherpa in Sikkim - Mataina, Wichamdinbo (Nepalese Linguistics, 2022)
The study is based on the primary data collected during 2017 and 2018 in Sikkim using the questionnaire designed by the Centre for Endangered Languages, Sikkim University.  Information about number of speakers, language vitality, domains of usage and causes of language endangerment were collected from the consultants who were both male and female from age 26 to 85 years with various occupational background. The study found that though the Sherpa speakers are positive towards their language, it is quite worrisome about the sustainability of Sherpa language in practice.